A turn-on fluorescence sensor based on Cu2+ modulated DNA-templated silver nanoclusters for glyphosate detection and mechanism investigation. (15th January 2022) - Yang, Yixia; Ghalandari, Behafarid; Lin, Liyun; Sang, Xiao; Su, Wenqiong; Divsalar, Adeleh; Ding, Xianting
Highlights: A new application of DNA-templated silver nanoclusters was reported. A turn-on fluorescence strategy based on Cu 2+ modulated DNA-templated silver nanoclusters were constructed for glyphosate detection. In this fluorescence sensor, we applied a stoichiometry method to investigate the mechanism of the fluorescence system. Determination of glyphosate in real samples was achieved. Abstract: The abuse application of glyphosate can result in a potential hazard for environment and human, however its ultrasensitive detection remains challenging. Herein, a Cu 2+ modulated DNA-templated silver nanoclusters (DNA-AgNCs) sensor was constructed to sensitively determine glyphosate based on the turn-on fluorescence strategy. The fluorescence quenching of DNA-AgNCs occurred with the existence of Cu 2+ . Upon the presence of glyphosate, the functional groups on the surface of glyphosate could chelate with Cu 2+, following the fluorescence recovery of DNA-AgNCs. Through the stoichiometric methods, we unveil that Cu 2+ -trigged fluorescence quenching mode is a combination of static and dynamic quenching with the static mode being predominant. In DNA-AgNCs/Cu 2+ system, the carboxylate, amine, and phosphonate groups of glyphosate interact with Cu 2+ through chelation, in which the carboxylate oxygen, the phosphonate oxygen atoms, and the monoprotonated secondary amine nitrogen atom and Cu 2+ form chelate rings. This fluorescence sensor showed a desired linearity of glyphosate analysis under the optimum conditions, ranging from 15 to 100 μg/L with a low detection down to 5 μg/L. Moreover, the proposed sensor was successfully utilized to measure glyphosate in real samples, indicating a promising application in pesticide residues detection.